Working mothers’ knowledge of exclusive breastfeeding in Hospital Canselor Tuanku Muhriz (HCTM) - Roziah Arabi; Rohani Mamat; Noraini Abd Rashid; Rufina Bakri (Penerbit Universiti Kebangsaan Malaysia, 2018)
Exclusive breastfeeding (EBF) is very crucial for the health of infant as well as mother. However, the prevalence of exclusive breastfeeding is very low especially among working mother. Since the prevalence of EBF might be influenced by the level of knowledge on EBF, researcher comes to critical thinking to conduct this study to evaluate level of knowledge on EBF among working mother. A cross sectional design study was carried out to determine knowledge level on exclusive breastfeeding among working mother, and its relationship with demographic data in Hospital Canselor Tuanku Muhriz (HCTM). A total 283 respondents were recruited to participate in this study. The respondents’ knowledge level on exclusive breastfeeding was identified using Kim & Chapman (2013) Questionnaire on Knowledge and Practice about Exclusive Breastfeeding. The result showed that majority of the respondents (56.9%) had high knowledge on exclusive breastfeeding. For demographic data, factors such as age, level of education, and family income had shown a significant association (p < 0.05) with level of knowledge on exclusive breastfeeding. In conclusion, the level of knowledge of EBF was identified among working mother, yet it has been influenced by mother’s sociodemographic background.